Response of n-nitrosodiethylamine-induced hepatocellular carcinoma to treatment with curcumin vs doxorubicin - Medeiros, Aldo Cunha; Medeiros, Aristela Sinara Constantino; Azevedo, Ítalo Medeiros; Celani, Lívia Medeiros; Souza, Thamires Barreto (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2019)
PURPOSE: Hepatocellular carcinoma (HCC) is a frequent and fatal human cancer with poor diagnosis that accounts for over half a million deaths each year worldwide. Curcumin has a wide range of pharmacological activities. This study aimed to investigate the chemopreventive and therapeutical effect of Curcumin against diethylnitrosamine (DEN)-induced HCC in rats. METHODS: HCC was induced in rats by a single injection of DEN (50 mg/kg) once a week, i.p., for four weeks. Group 1 rats were orally treated with curcumin two weeks prior to DEN injection that continued until the end of the experiment. Group 2 was treated with doxorubicin (0.72 mg/rat) and group 3 with saline. RESULTS: In the current study, a significant decrease in serum biomarkers of liver damage and cancer, including alfa-fetoprotein (AFP), gamma glutamyl transpeptidase (GGT), alanine transaminase (ALT), and aspartate transaminase (AST) was observed in curcumin-treated rats when compared to group 2 rats. The counting of red blood cells and leukocytes were significanty lower in doxorubicin group then in curcumin group (p<0.05). The relative weight of liver, a prognostic marker of HCC, was also reduced in curcumin group comparing with controls. No diference was observed comparing with doxo group rats. CONCLUSION: To conclude, our results clearly demonstrated that curcumin have a significant chemopreventive and therapeutical effect against primary liver cancer induced by DEN in rats. It can be suggested that the preventive activity of curcumin against hepatocarcinogenesis may have clinical relevance in further studies. KEY WORDS Hepatocellular carcinoma. Pharmacological treatment. Curcumin. Doxorubicin. Diethylnitrosamine. Rats